Pulmonary responses during the cycle-run succession in elite and competitive triathletes - Hue, O.; Galy, O.; Le Gallais, D.; Prefaut, C. (Canadian Journal of Applied Physiology, 2001)
Objectives: The purpose of this study was to determine the effect of performance level on the pulmonary responses in triathletes during the cycle-run succession. Methods: Eight regionally and nationally ranked (Competitive) and six internationally ranked (Elite) male triathletes underwent 30 min of cycling followed by 20 min of running (C-R) and 30 min of control cycling (C). Before and 10 min after each trial, the triathletes underwent lung function testing. Ventilatory data were collected every minute using an automated breath-by-breath system. Results: The results showed that (a) cycling induced a significant increase in residual volume and functional residual capacity in the Elite group (P < .05); (b) although cycling induced a significant decrease in DLCO in both groups, this decrease persisted at the end of the cycle-run exercise in the Competitive group only (P < .05); and (c) the rise in breathing frequency was significantly greater in the Competitive triathletes during the first 8 min of the subsequent run (P < .04). Conclusions: We conclude that the internationally ranked--or elite-performance--triathletes may have developed specific responses to the cycle-run succession.